2022
DOI: 10.1111/1462-2920.16024
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis study of the robustness and universality of gut microbiota–shrimp diseases relationship

Abstract: Intensive case study has established dysbiosis in the gut microbiota-shrimp disease relationship; however, variability in experimental design and the diversity of diseases arise the question of whether some gut indicators are robust and universal in response to shrimp health status, irrespective of causal agents. Through an unbiased subject-level meta-analysis framework, we re-analysed 10 studies, including 261 samples, four lifestages and six different diseases (the causal agents are virus, bacterial, eukaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…Selection is a deterministic process that includes homogeneous selection (e.g., host filtering) and variable selection (e.g., heterogeneity of the local environment) (Chase & Myers, 2011). Notably, the relative importance of deterministic processes that govern the gut microbiota in diseased shrimp was consistently lower than that in corresponding healthy controls (Figure 3), thus supporting the findings in previous studies (Sha et al, 2022; Zhu et al, 2016). The occurrence of diseases could weaken host filtering on external taxa, resulting in a compromised homogeneous selection (Xiong et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Selection is a deterministic process that includes homogeneous selection (e.g., host filtering) and variable selection (e.g., heterogeneity of the local environment) (Chase & Myers, 2011). Notably, the relative importance of deterministic processes that govern the gut microbiota in diseased shrimp was consistently lower than that in corresponding healthy controls (Figure 3), thus supporting the findings in previous studies (Sha et al, 2022; Zhu et al, 2016). The occurrence of diseases could weaken host filtering on external taxa, resulting in a compromised homogeneous selection (Xiong et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Ample evidence has shown that shrimp lifestages, different diseases, hypervariable regions and sequencing platforms, are driving factors shaping the gut microbiota (Cornejo‐Granados et al, 2018; Garcia‐Lopez et al, 2020; Sha et al, 2022). These biotic and technical variables complicate the identification of common gut microbiota features that characterise diverse shrimp diseases, although this knowledge is fundamental to uncover etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis demonstrated that supervised learning models for soil microbiomes may be used to predict the potential occurrence of Fusarium wilt disease in plants ( Yuan et al., 2020 ). In addition, supervised learning methods have identified robust and reproducible features relevant for diagnosing shrimp diseases according to meta-analyses of gut microbiota ( Sha et al., 2022 ). The origin and quality of sea cucumber cultured in diverse geographic regions has also been accurately predicted using random forest models for gut microbiota ( Zhao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond immunological and morphological development, progressive exposure and interaction with the external environment associated with shrimp development also results in dynamic temporal succession of shrimp microbiota composition. 63,73 The dynamics of the microbiome are associated with shrimp health and immune capacity, 74,75 thus, changes in its composition and diversity during ontogenesis may further influence disease susceptibility. 37,76,77 Characterisation and analysis of the microbiome is yet to become a standard practice in PCE studies and currently remains cost-prohibitive in many instances.…”
Section: Developmental Stage-sizementioning
confidence: 99%